STUDI PERBANDINGAN ANTARA KOMUNIKASI TOTAL DENGAN EJAAN JARI DALAM MENINGKATKAN KEMAMPUAN MEMBACA TEKNIS BAGI SISWA TUNARUNGU KELAS III /B DI SLB KARTINI BATAM - Abulaesi - - (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this study was to prove the presence or absense of total communication influence on the ability to read the announcement  with proper pronunciation and intonation for deaf students in special-ed classes D.III/B Kartini Batam. This study uses quasi experiment with the rotation patern (the experimental group and the control group). The sample was third grade deaf student, amounting to 8 people. Data obtained through test the ability to read the announcement. Then analyzed with the Mann-Whitney test. The result showed that Uc =7 and Ut= 15, so the statistical decision: Uc < Ut (7< 15). Means the null hypothesis (Ho) is rejected and accepted (H1). These result can be concluded that the level of 95% of the data obtained can be said that “the ability to read the announcement of the third grade deaf children in special schools are not the same Batam Kartini (no influence) after being given a lesson by using total communication”. The results also that effect result from childre eith communication learnning total is positive (increasing returns) than child with spelling. Thus, it can be suggested at the school, teachers and researchers to further use total communication in learning to read more